Oscar Wilde's the happy prince - Grodin, Elissa, 1954-; Stutzman, Laura; Wilde, Oscar, 1854-1900. (Chelsea, MI : Sleeping Bear Press, 2006)
A beautiful, golden, jewel-studded statue and a little swallow give all they have to help the poor.
Horn Book
4.3
K-3.
K-3
Keywords: Fairy tales; Fairy tales